2021
DOI: 10.5430/wje.v11n1p94
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Indicators for Transformational Leadership of Undergraduate Students at Thailand National Sports University

Abstract: This paper develops indicators for transformational leadership of undergraduate students at Thailand National Sports University. The development of these indicators was based on in-depth interviews with six informants. The research instrument was a semi-structured interview form. The data collected were inductively analyzed. The development of indicators was accomplished through the synthesis of the data and the conceptual framework for this research investigation. Evaluate indicators of Accuracy Standard Prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
(22 reference statements)
1
0
0
2
Order By: Relevance
“…However, it has been determined that pre-service teachers did not have an idea about technology and technological developments in the Industrial Age 4.0 (Bolat & Baş, 2018). This result is consistent with Sukdee (2021), who showed that students should have transformational leadership consisting of idealized influence, inspiration motivation, intellectual stimulation, and individualized consideration to prepare for economic changes in society and technology.…”
Section: Introductionsupporting
confidence: 54%
“…However, it has been determined that pre-service teachers did not have an idea about technology and technological developments in the Industrial Age 4.0 (Bolat & Baş, 2018). This result is consistent with Sukdee (2021), who showed that students should have transformational leadership consisting of idealized influence, inspiration motivation, intellectual stimulation, and individualized consideration to prepare for economic changes in society and technology.…”
Section: Introductionsupporting
confidence: 54%
“…Otras variables encontradas son el Empoderamiento psicológico (Amjad et al, 2022;Fauzi et al, 2021), Comportamiento emprendedor/Perfil del emprendedor (Álava-Atiencie & Quinde-Lituma, 2023;Fauzi et al, 2021), Habilidades sociales/competencias socioemocionales (Álamo & Falla, 2022;Tenorio, 2021) y Personalidad (Lamm et al, 2014;Perreault et al, 2016). Por último, se hallan variables poco estudiadas como Identidad global y local (Lisak & Harush, 2021), Apoyo a las necesidades psicológicas (Perreault et al, 2016), Estrategias de intercambio de conocimiento (Fauzi et al, 2021), Motivación del estudiante (Lee et al, 2022) y la Elaboración de indicadores de LT (Sukdee, 2021), que es un estudio instrumental.…”
Section: Diseño De Investigación Variables Estudiadas Muestra Instrum...unclassified
“…Además, dentro de los instrumentos psicométricos hallamos a la Encuesta de Orientaciones de Liderazgo de Bolman y Deal (1990, en Devecioğlu, 2018, Liderazgo Transformacional Global (GTL) de Carless et al (2000, en Perreault et al, 2016, la Encuesta de Liderazgo Transformacional (TLS) de Clark (2011;Amjad et al, 2022), Escala de Liderazgo transformacional validado por Rafferty & Griffin (2004, en Salanova et al, 2022 y la Escala MLIS de Cárdenas (2016, en Tenorio, 2021) de origen peruano con 4,76% (1 artículo) en cada caso. Por otro lado, se aprecia un Cuestionario de indicadores de LT, el cual fue elaborado por Sukdee (2021). Por último, se puede apreciar en la Tabla 2 que se elaboraron otras herramientas o estrategias para medir el liderazgo transformacional como Pruebas de conocimiento (Pascal et al, 2017) y Análisis de ensayos (Lee et al, 2022).…”
Section: Diseño De Investigación Variables Estudiadas Muestra Instrum...unclassified